2020
DOI: 10.14203/bkr.v23i2.266
|View full text |Cite
|
Sign up to set email alerts
|

Struktur Anatomi Daun Sebagai Bukti Dalam Pembatasan Takson Tumbuhan Berbunga: Studi Kasus 12 Suku Tumbuhan Berbunga Indonesia

Abstract: Keanekaragaman tumbuhan tidak hanya terlihat secara morfologi, tetapi dapat dibedakan pula secara anatomi. Ciri anatomi dapat digunakan sebagai pendukung dan penguat pengklasifikasian jenis tumbuhan. Penelitian ini bertujuan untuk mengetahui ciri anatomi daun yang dapat digunakan sebagai penciri taksonomi dalam suatu tingkatan taksa melalui perwakilan jenis. Jenis yang digunakan berjumlah 15, yang merupakan perwakilan dari 12 suku tumbuhan berbunga Indonesia. Metode parafin digunakan untuk mendapatkan penampan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
3
0
3
Order By: Relevance
“…Based on observations of leaf anatomy (Figure 1 to Figure 6) the mesophyll of all six dicot ornamental plants had differentiated into palisade and spongy tissue which was linear with the statements of Sumardi and Pudjoarinto (1992) who cited that mesophyll in all dicot ornamental plants had been differentiated into palisade and spongy tissue. The complete dicots leaves anatomical tissue comprised of upper and lower epidermal tissue, and the mesophyll which was composed of palisade and spongy tissue (Tihurua et al, 2020). The results showed that all plants had one layer of upper and lower epidermis tissue (Figure 1 to Figure 6).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Based on observations of leaf anatomy (Figure 1 to Figure 6) the mesophyll of all six dicot ornamental plants had differentiated into palisade and spongy tissue which was linear with the statements of Sumardi and Pudjoarinto (1992) who cited that mesophyll in all dicot ornamental plants had been differentiated into palisade and spongy tissue. The complete dicots leaves anatomical tissue comprised of upper and lower epidermal tissue, and the mesophyll which was composed of palisade and spongy tissue (Tihurua et al, 2020). The results showed that all plants had one layer of upper and lower epidermis tissue (Figure 1 to Figure 6).…”
Section: Discussionmentioning
confidence: 94%
“…Leaves are one of the important organs of plants that function as a place of photosynthesis (Campbell et al, 2008). Leaves comprise of upper and lower epidermal tissues, mesophyll (palisade and spongy) tissues, and transport bundles (Wulansari et al, 2020). Each tissue gives a different appearance and provide special features so that the anatomical features can be used as a supporting tool in the identification, grouping, and kinship of plant species (Stuessy, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…malaccensis. Druses could be used as a diagnostic character to identify Garcinia species, as observed in Garcinia morella, Garcinia spicata (Pathirana & Herat, 2004), G. madruno (Abreu et al, 2017), G. indica (Priya & Hari, 2019), Garcinia dioica (Wulansari et al, 2020), and G. dulcis (Begum, 2020). All of these Garcinia species exhibited a similar appearance of druses.…”
Section: Resultsmentioning
confidence: 99%
“…Karakter ini dapat berubah seiring perubahan kondisi lingkungan (Rindyastuti, 2017). Semakin tinggi suhu lingkungan dan menurunnya kadar air maka densitas stomata akan semakin rendah kerapatan stomata pada tumbuhan (Wulansari, 2019). Hal ini menunjukkan adaptasi tumbuhan untuk meminimalkan kehilangan air melalui transpirasi (Ziraluo, 2020).…”
Section: Pendahuluanunclassified